HotSHOT Extraction Is a Fast, Economical, and Efficient Method for Obtaining Tardigrade gDNA - Cuauhtemoc F. Amezcua-Martínez; Andrea R. Jiménez-Marín; Alba R. Dueñas-Cedillo; José J. Flores-Martínez; Zulema Gomez-Lunar; Enrico A. Ruiz; Francisco Armendáriz-Toledano (Psyche: A Journal of Entomology)
Among the main problems in obtaining genomic DNA (gDNA) from small invertebrates such as tardigrades are the low amount of gDNA obtained per specimen, as well as the complexity of steps and number of reagents used for gDNA extraction. For example, the extraction method with chelating resin is the most used as an alternative to commercial kits for tardigrades; however, the chelating resin can inhibit the PCR. Other more expensive alternatives, as in the case of commercial kits, several washing and purification steps are required, leading to low gDNA content or even loss. Therefore, more viable methods have been developed to obtain tardigrade gDNA, such as the extraction method by alkaline lysis HotSHOT. This study compares the HotSHOT extraction method with commercial kits (Qiagen kit) and chelating resin methods. According to our results, we showed that the HotSHOT method allows to recover more amplicons from unpurified gDNA extractions compared to the chelating resin method. As to the gDNA integrity, with the HotSHOT method, the quantity of amplicons is similar to that obtained with the Qiagen kit, but easier to implement. In terms of purity (absorbance ratio A260/280), the extraction method with the Qiagen kit obtained higher values of optimal purity. It was also shown that the spin-column purification method is better than the paramagnetic beads purification method, because the latter did not allow to obtain amplicons by PCR. Given its yield, purity, simplicity, time, and cost, the HotSHOT method appears to be the most efficient for obtaining tardigrade gDNA.